Joint attention and exogenous attention allocation during mother-infant interaction at 12 months associate with 24-month vocabulary composition - Capelli, Elena; Grumi, Serena; Vercellino, Luisa; Provenzi, Livio (Frontiers in Psychology, 2025)
IntroductionEarly attentional processes are inherently linked with early parent-infant interactions and play a critical role in shaping cognitive and linguistic development. This study explored how specific early attention mechanisms-namely, exogenous attention allocation and joint attention initiation-during mother-infant interactions at 12 months may influence language development at 24 months.MethodsA sample of 46 typically developing children was observed at 12 months during mother-infant interactions obtained through remote videotaping. Quantitative measures of exogenous attention allocation to external auditory stimuli and joint attention initiation by the infant were obtained through micro-analytical coding. Language outcomes were assessed at 24 months, with a focus on vocabulary composition (i.e., percentage of predicates).ResultsFindings showed significant negative associations between early life exogenous attention allocation and later vocabulary composition (i.e., predicate percentage). This association was modulated by joint attention initiation: infants displaying lower levels of joint attention initiation showed a negative association between exogenous attention allocation and language development.DiscussionThe findings are suggestive of a complex relationship among different forms of early attention skills and language development in the first 2 years of life.